IMPLEMENTATION OF GOOD CORPORATE GOVERNANCE AT PT AXA MANDIRI FINANCIAL SERVICES - Hotimah, Hudriatul (Dinasti International Journal of Digital Business Management, 2020)
Good Corporate Governance (GCG) is a system that organizes and controls a company so that it can form added value for all stakeholders. This study aims to determine the application of GCG at PT AXA Mandiri Financial Services (AMFS) which is a joint venture Conventional Life Insurance company between PT Bank Mandiri (Persero) Tbk and National Mutual International Pty. Limited (AXA). The research method used is descriptive qualitative. The results of this study indicate that PT AMFS has implemented GCG in an integrated manner in all business processes. This is evidenced by the transformation in 10 line areas, namely digital services, distribution, health and protection, human resources and culture, information technology systems, data, efficiency, customer experience, and offers (documents and products). PT AMFS also applies the Three Lines of Defense principle to an internal control system that is integrated with risk management. The main line of defense is the directors and all employees of PT AMFS. Second, risk management, compliance and law. Third, internal and external audit.